ANALISIS KINERJA KEUANGAN DAN FINANCIAL DISTRESS PADA BANK ASING DAN BANK UMUM SWASTA NASIONAL DEVISA DI INDONESIA - Melinda Dwi Putri; Dwi Susilowati (Jurnal Ilmu Ekonomi JIE, 2018)
The purpose of this research is to find out and to analyze the financial performance and potential bankruptcy of foreign banks and national private foreign-exchange commercial banks in Indonesia. The data collection in this research used secondary data which obtained from the financial statements contained on the website of foreign and national private foreign-exchange commercial banks The data analysis used CAEL ratio and Altman Z-Score model as a technique to collect the data. The CAEL ratio which Capital Adequancy Ratio (CAR), Assets Quality (KAP), Return On Assets (ROA), Operating Expenses to Operating Income (BOPO), and Loan to Deposit Ratio (LDR) The results of this research indicate that by using CAEL ratio obtained 7 foreign banks and 30 national private foreign-exchange commercial banks that have healthy criteria, 2 national private foreign-exchange commercial banks that have sufficiently healthy criteria, and 1 national private foreign-exchange commercial bank that have less healthy criteria, while using Altman Z-score model obtained 2 foreign banks and 1 national private foreign-exchange commercial bank that have predicate not potential to bankrupt, 3 foreign banks and 17 national private foreign-exchange commercial banks that have predicate potentially bankrupt, and 2 foreign banks and 15 national private foreign-exchange commercial banks predicted bankrupt.Keywords: Financial Performance, Financial Distress, Foreign Bank, Foreign Exchange Bank.